Neuropsychological assessment of the decision making process in children and adolescents: an integrative review of the literature (Archives of Clinical Psychiatry, 2011)
OBJECTIVE: Nowadays there has been growing interest in the "hot" aspects of the executive functions related to the orbitofrontal cortex (OFC), in particular in the affective decision-making process in children and adolescents. We reviewed the available literature about the evaluation of decision making in children and adolescents. METHOD: We searched for papers published from 2000 to 2009 that studied children and/or adolescents until the age of 16 in the Lilacs and PubMed index. The papers were analyzed according to the paradigms used in the studies, the conclusions about the development of the decision-making process, and the ability to distinguish between the clinical population and the controls. RESULTS: Thirty-six papers were selected. Compared to the amount of studies of adults, there are still few studies focusing on children and adolescents. Several versions derived from the IGT were developed in order to study decision-making processes in children and adolescents. DISCUSSION: The IGT is the most used instrument. In preschoolers, simplified versions have been used with greater frequency. The different paradigms are useful in differentiating between normal and psychiatric disorder patients. The results are positively and significantly related to the frequency of impulsive behaviors in nonclinical populations.